The Relevance of Indonesia's Ratification of the International Convention Against the Taking of Hostages - Veda, Malinda Benita; Surwandono, Surwandono (Nation State: Journal of International Studies, 2025)
Hostage-taking cases involving Indonesian citizens, both domestically and abroad, remain a persistent challenge for the Indonesian government in ensuring citizen protection and safeguarding national sovereignty. Although previous studies have examined diplomatic approaches such as total diplomacy and the duty of care principle, limited research has examined how media discourse shapes public perception of policy urgency regarding the ratification of the International Convention Against the Taking of Hostages (ICATH). This study aims to explore dominant media narratives, frames, and thematic patterns that shape public discourse on ICATH ratification. A qualitative research design was employed using thematic coding within an inductive–deductive framework. Data were collected from 100 national online news articles published between 2011–2025. The analysis followed three coding stages: open coding, axial coding, and selective coding. Findings show contrasting media tendencies. Independent media emphasise regulatory weaknesses, legal gaps, and the urgency of strengthening international legal commitments, while state-affiliated media highlight diplomatic engagement, crisis management, and government responsiveness. The study argues that Indonesian media play an active role in shaping policy legitimacy by reinforcing issue framings rather than merely reporting events. Ratification is a strategic imperative to align public expectations, strengthen protection, and reinforce Indonesia’s global role in cooperation.